How does mobile business create value for firms? - Picoto, Winnie Ng (2022)
Mobile business is expected to create a large spectrum of business opportunities. There are many studies analyzing the contribution of IT to firm performance and whether IT is capable of creating value. One process-level model of IT business value, defined as the contribution of IT to firm performance, focuses on how IT impacts critical business activities within the firm’s value system (in the context of the firm’s value chain). Building on these concepts, we argue that the m-business value corresponds to the impact of m-business usage on firm performance, which is estimated through the perceived impact on the three major groups of activities on the value chain: (i) downstream dimension, (ii) upstream dimension, and, (iii) internal operations. We claim that m-business leverages the potential of the unique features of mobile technologies to improve business performance. This paper is exploratory and aims at answering the following research questions: (i) How does m-business create value to firms? and (ii) Which are the components of the construct m-business value for firms? Interviews were conducted with experts to explore the construct of m-business value and its components. The interviews’ results show that m-business does have impacts on the organizational downstream and internal dimensions. However, its impacts on upstream dimensions are not clear yet. We discuss the implications of these findings for future research and the limitations of the current study.